# Perform the operation and get your answer in the form a + bi. (3 + 2i)(2 - 4i)

### 2 Answers | Add Yours

Use foil method.

First terms: 3 * 2 = 6.

Outer terms: 3*-4i = -12i

Inner terms: 2i*2 = 4i

Last terms: 2i*-4i = -8i^2

So, we will have:(3 + 2i)(2 - 4i) = 6 - 12i + 4i - 8i^2

Combine like terms, and take note that i^2 = -1.

6 - 12i + 4i - 8i^2 = 6 - 8i -8(-1) = 6 - 8i + 8 = 14 - 8i

Therefore,** final answer is 14 - 8i**.

`(3+2i)(2-4i)=(3.2-3.4i+2i.2-2i.4i)`

`=(6-12i+4i-8i^2)`

`=(6-8i-8.(-1))` Since `i^2=-1`

`=(6-8i+8)`

`=(14-8i)` . Answer.